Disciplining the millennial generation through Islamic boarding school activities in the formation of character - Abdunnasir, Abdunnasir (Journal Sains and Education, 2023)
Islamic boarding schools are one of the social educational institutions that play an active role in creating character empowerment and in shaping the morals of young generations, contributing to social and religious aspects. The aim of efforts to increase the discipline of students through habituation activities at Islamic boarding schools is a process or way to create a habit or disciplinary behavior. And the attitude of discipline will be reflected in the existence of obedience to respect and implement a system that requires people to submit to the decisions, orders and regulations that apply. Therefore this research was conducted to explore Disciplining the millennial generation through Islamic boarding school activities in the formation of character. Where this research is a literature source, with this type of qualitative research.